Cover your eyes [large type] - Burton, Mary (Mary T.) (Center Point Large Print, 2015)
"Motivated by her brother's unlawful conviction and subsequent death in prison, public defender Rachel Wainwright requests a DNA test for a man who was sent to prison thirty years ago for a murder he claims he didn't commit. Concerns rise when a new string of similar murders occur"--